EFFECT OF BIOMASS OF AZOLLA MICROPHYLLA ON CHEMICAL OF WATERQUALITY PARAMETERS ON PEAT SOIL MEDIAS - Khairuniah Khairuniah; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted from February to April, 2018 in the Peatland of Kualu Nenas Village, Kampar District, Riau Province. Objective of this study was determine the effect of biomass of Azolla microphylla on the chemical water parameters of peat soil ponds. Method of this researchwas used on experimental, used Complete Randoimned Desaign (CRD) for one factor 4 treatements P0 (without biomass of A. microphylla), P1 (20 g/m2), P2 (40 g/m2), and P3 (60 g/m2) and 5 replications.The result showed that the A. microphylla significantlyaffected to chemical parameters of peat soil and water than dose of P3(60 g A. microphylla/m2) also the water chemical parameters was able to increase is pH 5-7,5, DO 3,2 – 7,16 mg/l, CO2 18,37- 33,30mg/l, Nitrate0,76 – 4,42 mg/l, and Orthophosphate 1.41 - 3.87 mg/l. Keyword: Azolla microphylla, Chemistry water Parameters Peat